Comparison of serum procalcitonin level with erythrocytes sedimentation rate, C-reactive protein, white blood cell count, and blood culture in the diagnosis of bacterial infections in patients hospitalized in Motahhari hospital of Urmia (2016) - Amir Nasimfar; Ebrahim Sadeghi; Mohammad Karamyyar; Laya Javan Manesh (Wolters Kluwer Medknow Publications, 2018)
Blood infection is one of the causes of morbidity in hospitalized patients. While some scholars have identified procalcitonin (PCT) as a potential biomarker for the diagnosis of blood infection, others have questioned its diagnostic value. Thus, the present study was conducted to compare the diagnostic values of PCT with C-reactive protein (CRP), erythrocytes sedimentation rate (ESR), white blood cell (WBC) count, and blood culture in patients with bacterial blood infections. In a prospective case-control study, 45 septic patients (6 months-5 years old), who were hospitalized in Shahid Motahhari Hospital of Urmia over the year 2016 and 45 patients with noninfectious diseases, whose gender and age range were similar to the members of the septic group, were examined. The participants' blood samples were taken for the sake of blood culture and measurement of PCT level, ESR, and CRP. Finally, the collected data were analyzed through the SPSS-21 software. the results indicated that the average PCT, ESR, CRP, and WBC count was significantly higher in septic patients. Moreover, the blood culture of patients with negative or intermediate serum PCT levels was negative, while 50% of blood culture results in patients with positive PCT were positive and the rest were negative. Finally, a significant relationship was detected between the frequency of blood culture results and results of serum PCT tests (P = 0.003). serum PCT level can be considered a diagnostic marker of bacterial infections. If used in conjunction with tests of CRP, ESR, and WBC count, the PCT test can enhance the diagnosis of bacterial infections.